Stabilization of the actomyosin ring enables spermatocyte cytokinesis in Drosophila. - Goldbach, P.; Wong, R.; Beise, N.; Sarpal, R.; Trimble, W.S.; Brill, J.A. (Molecular Biology of the Cell, 2010)
The scaffolding protein anillin is required for completion of cytokinesis. Anillin binds filamentous (F) actin, nonmuscle myosin II, and septins and in cell culture models has been shown to restrict actomyosin contractility to the cleavage furrow. Whether anillin also serves this function during the incomplete cytokinesis that occurs in developing germ cells has remained unclear. Here, we show that anillin is required for cytokinesis in dividing Drosophila melanogaster spermatocytes and that anillin, septins, and myosin II stably associate with the cleavage furrow in wild-type cells. Anillin is necessary for recruitment of septins to the cleavage furrow and for maintenance of F-actin and myosin II at the equator in late stages of cytokinesis. Remarkably, expression of DE-cadherin suppresses the cytokinesis defect of anillin-depleted spermatocytes. DE-cadherin recruits beta-catenin (armadillo) and alpha-catenin to the cleavage furrow and stabilizes F-actin at the equator. Similarly, E-cadherin expression suppresses the cytokinesis defect caused by anillin knockdown in mouse L-fibroblast cells. Our results show that the anillin-septin and cadherin-catenin complexes can serve as alternative cassettes to promote tight physical coupling of F-actin and myosin II to the cleavage furrow and successful completion of cytokinesis.